THE IMPACT OF RENOVATING THE OLD BANTEN AREA AS A TOURISM DESTINATION - Titi Stiawati; Ima Maisaroh; Suja’i (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
Impact of Renovation of Banten Lama Area as a Tourist Attraction Destination. Renovation is the repair of partially damaged buildings with the aim of using them according to certain functions, which can remain or change both architecture, structure and utilities. The purpose of this study is to determine the impact of renovation of Banten Lama area and as a tourist attraction destination. The research method used is qualitative research method. That is research conducted naturally in accordance with conditions in the field without technical planning, and the type of data collected is descriptive data. Data collection techniques were carried out by face-to-face interviews with visitors and traders in the Banten Lama area, in structured interviews where researchers sequentially formulated questions and recorded the answers of the speakers. The results of this study show that with the improvement of infrastructure and accessibility, visitors can more easily enjoy and explore the area, this can increase the number of visits and duration of stay of tourists, and this renovation can revive historical sites, and increase people's interest in learning about the history and culture of the area. This can attract tourists who are interested in cultural heritage.